(untitled) (Research, Society and Development, 2022)
Attention Deficit Hyperactivity Disorder presents in its history and description complexities of meanings, concepts and some controversies. I consensus on the description occurs in general, but from the neuro-psychiatric point of view, some scientists have disagreements, which influenced the history of the disorder as well as its evolutionary process as a pathology. In this perspective, the present study proposes to describe the history of the disorder, pointing out some specificities and contradictions. To this end, the methodology used in this study is qualitative, in relation to the objectives, it is an exploratory and descriptive research and referring to the research procedures, the study was characterized as bibliographic. The research was carried out in a virtual environment, in reliable databases such as Scielo, with scientific articles and books in pdf format, with the descriptors ADHD, history and evolution, which generated results and discussion divided into three topics: general considerations, historical context and evolution and some notes. The final considerations comprise the author’s impressions and conclusions.